A remarkable curiosity : dispatches from a New York City journalist's 1873 railroad trip across the American West - Cummings, Amos J. (Amos Jay), 1841-1902 (University Press of Colorado, 2008)
Collected in this volume for the first time are Cummings's portraits of a land and its assortment of characters unlike anything back East. Characters like Pedro Armijo, the New Mexican sheep tycoon who took Denver by storm, and more prominently the Mormon prophet Brigham Young and one of his wives, Ann Eliza Young, who was filing for divorce at the time of Cummings's arrival. Although today he is virtually unknown, during his lifetime Cummings was one of the most famous newspapermen in the United States, in part because of stories like these. Complete with a biographical sketch and historical introduction, A Remarkable Curiosity is an enjoyable read for anybody interested in the American West in the latter half of the nineteenth century.